The effects of participation in global value chains on energy intensity: Evidence from international industry-level decomposition - Zhida Jin (Elsevier, 2022)
This paper investigates how industries' participation in global value chains (GVCs) affects their own energy intensity. Both industries' GVCs position and GVCs participation degree are constructed to describe the characteristics of industries' participation in GVCs. We first provide a theoretical analysis on the impacting mechanism of industries' participation in GVCs on energy intensity. Then a panel data of 56 industries in 42 countries over the period 2000 to 2014 is used for empirical tests. The results show that the promotion of industries' GVCs position has significantly reduced their own energy intensity, while the effect of industries' GVCs participation degree on that is ambiguous. The improvement of the industrial internal structure and technology progress are the main channels through which the promotion of GVCs position reduces energy intensity. Compared to backward GVCs position, the change of forward GVCs position has a greater impact on energy intensity. Moreover, for developed countries, the deepening of GVCs participation degree reduces manufacturing industries' energy intensity, whereas for developing countries, the deepening of GVCs participation degree increases manufacturing industries’ energy intensity, which verifies the pollution haven hypothesis to some extent.